Igniting Wonder : Plays for Preschoolers - Adams, Elissa; Brosius, Peter (Book collections on Project MUSE., 2013)
Young children love to explore their world through drama--characters, dialogue, story arcs, and props are all standard elements of a child's play. It is no surprise then that professional theatre has long been regarded as a way to support children's social-emotional, cognitive, and creative development. Increasingly, there is an international interest in theatre for very young audiences, and the Wall Street Journal reported on a "baby boom" in American theatre, with a marked upswing in the number of stage plays being written and produced for toddlers and preschoolers. Fueled by ongoing research into developmental psychology and theatre arts, the Children's Theatre Company (C.T.C.) of Minneapolis presents in this book four of its newly commissioned plays for preschoolers. C.T.C. is widely recognized as the leading theatre for young people and families in North America; it received the 2003 Tony award for regional theatre, and Time magazine rated it the number one children's theatre in the United States. These four plays encompass a broad range of styles and subjects: Bert and Ernie, Goodnight! is a musical about Bert and Ernie's unlikely but true friendship, written by Barry Kornhauser and based on the original songs and scripts from Sesame Street. The Biggest Little House in the Forest is a toy-theatre play about a group of diverse animals trying to share a very tiny home, adapted by Rosanna Staffa from the book by Djemma Bider. The Cat's Journey is a dazzling shadow-puppet play with a little girl who rides on a friendly cat, written by Fabrizio Montecchi. And Victoria Stewart's Mercy Watson to the Rescue!, adapted from the Kate DiCamillo Mercy Watson series, is a comic romp featuring the inadvertent heroics of everyone's favorite porcine wonder. While these plays are as different as they could be, they all help young children to develop a moral compass and critical-thinking skills--while also showing them the power of the theatre to amaze, delight and inspire